Prevalence of Musculoskeletal Injuries in New Zealand Army Recruits as Defined by Physical Therapy Service Presentations. Issue 1 (15th May 2021) - Hall, Narelle; Constantinou, Maria; Brown, Mark; Beck, Belinda; Kuys, Suzanne
ABSTRACT: Introduction: Army recruit injuries occurring during basic training can lead to high personal and organizational burdens potentially threatening deployment capability. Previous military surveillance describing recruit injury as defined by physical therapy presentations is limited to 1-year duration or includes only male infantry recruits or trained personnel. Research describing injury incidence and trends specific to New Zealand Army basic training recruits over a longer period will better inform future injury prevention programs. Aims: To identify the incidence and patterns of injuries reported from physical therapy presentations for New Zealand Army recruits undertaking basic training over a 4-year period. Materials and Methods: This retrospective observational study identified injuries from physical therapy service presentations in New Zealand Army recruits from 2008 to 2011. All male and female New Zealand Army recruits who presented to physical therapy, following medical triage, were included. Recruit physical therapy presentations for injury and respiratory and other conditions were collated. Injury incidence was grouped by body region (upper limbs, lower limbs, and combined spinal regions) and site (joint or segment), and cumulative and injury incidence rates were calculated. Results: One thousand eight hundred and ninety-six (1, 697 males and 199 females) New Zealand Army recruits commenced basic training between 2008 and 2011. One thousand six hundred and eighty-three physical therapy presentations occurred for recruit injury during New Zealand Army basic training over 4 years. Lower limb injuries accounted for over 75% ( n = 1, 285) of the overall demand for physical therapy service during recruit basic training. Injuries sustained at the knee and below accounted for 67% of all reported injury presentations. Conclusion: Four years of injury surveillance using physical therapy presentations identified the lower limb, with the knee and below as the most commonly injured regions in New Zealand Army recruits. Injury prevention interventions for New Zealand Army recruits should aim to reduce lower limb injuries. Future research on injury surveillance would benefit from incorporating clear injury and severity definitions, established injury classification systems, and standardized incidence calculations.